1997
DOI: 10.17986/blm.199722226
|View full text |Cite
|
Sign up to set email alerts
|

Trakya Üniversitesi Tıp Fakültesi Acil Servisine Başvuran Adli Olguların Özellikleri

Abstract: T h e c h a r a c t e r i s t ic s o f th e c a s e s w h ic h a d m itte d to E m e r g e n c y D e p a rtm e n t o fT ra k y a U n iv e rs ity M e d ica l F a c u lty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 1 publication
0
5
0
15
Order By: Relevance
“…The higher rate of medico-legal trauma among this population may be due to young men working high-risk jobs, and spending more time driving and engaged in social life [12,13]. A study by Altun et al, [14] reported that traumatic medico-legal cases increase during the summer months. Turla et al, [6] report that medico-legal cases occur at the lowest frequency during the winter months.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rate of medico-legal trauma among this population may be due to young men working high-risk jobs, and spending more time driving and engaged in social life [12,13]. A study by Altun et al, [14] reported that traumatic medico-legal cases increase during the summer months. Turla et al, [6] report that medico-legal cases occur at the lowest frequency during the winter months.…”
Section: Discussionmentioning
confidence: 99%
“…Günlük olaylarda ve travmalarda erkek cinsiyetin daha fazla rol oynaması nedeniyle erkeklere kadınlara göre %58 ila %78 arasında daha fazla adli olgu olarak karşılaşıldığı bildirilmektedir (7)(8)(9)(10). Mevsim şartları nedeniyle trafik kazası, düşme, intihar gibi dış etmenlerle karşılaşma sıklı-ğı fazla olan yaz aylarında daha sık karşılaşılmaktadır (1,3,11).…”
Section: Discussionunclassified
“…Assault-induced forensic cases are reported among the first four causes in neglect and abuse series and the incidence is reported to be between 6% and 19% in various studies 22, 23, 24, 25, 26, 27. These cases were suspected due to the presence of traces of old bruises and burns, contradictory statements of family, fussy family members, accompanying old lesions to new, children being taken to emergency department by different family members and prior admission due to multiple trauma and physical abuse was demonstrated in these patients.…”
Section: Discussionmentioning
confidence: 99%